PENGARUH PENDIDIKAN KESEHATAN TENTANG MENARCHE DAN PERUBAHAN FISIK SEKUNDER MELALUI METODE TEMAN SEBAYA ( PEER GROUP) TERHADAP PERSEPSI REMAJA PUTRI DALAM MENGHADAPI MENARCHE DI SDN KAMPUNG DALEM 6 KOTA KEDIRI - Dessy Lutfiasari (STRADA : Jurnal Ilmiah Kesehatan, 2016)
Results of a preliminary study of the perceptions of young women in the face of menarche in SDN Kampungdalem 6 Kediri is from 10 students 7 (70%) showed the negative reaction that they f eel confused and scared while getting menarche. Based on the above data it can be seen that there are many young women who have negative perceptions of menarche. The purpose of this study was to determine the effect of health education about menarche through methods of peer group (peer group) on the perception of young women in the face of menarche in SDN Kampungdalem 6 of Kediri in 2014. This study is the kind of research quasy experiment with this type of survey design and with the aim comparison. The research subject that is all the young women in SDN Kampungdalem 6 aged 10-13 years and have not gotten menarche in April 2014. Sampling took using simple random sampling. Number of samples was 32 adolescent girls. The results showed that the perception of girls before being given health education about menarche through methods of peer group (peer group), the majority of respondents (56.3%) have a good perception about menarche. Meanwhile, after health education, nearly all respondents (93.8%) had a good perception in the face of menarche. The results of the data analysis of statistical tests Mc.Nemar obtained p = 0.031 with α = 0.05. Where p <0.05 which means that h0 h1 rejected and accepted, so that it can be concluded that there is influence of menarche health education through the method of peer group (peer group) on the perception of young women in the face of menarche in SDN Kampungdalem 6 Kediri in 2014. Based on the results for research can improve the provision of information about menarche through the peer group to girls before getting menarche